Small-Colony Mutants of Staphylococcus aureus Allow Selection of Gyrase-Mediated Resistance to Dual-Target Fluoroquinolones - Pan, Xiao-Su (American Society for Microbiology, 2002)
Fluoroquinolones acting equally through DNA gyrase and topoisomerase IV in vivo are considered desirable in requiring two target mutations for emergence of resistant bacteria. To investigate this idea, we have studied the response of Staphylococcus aureus RN4220 to stepwise challenge with sparfloxacin, a known dual-target agent, and with NSFQ-105, a more potent sulfanilyl fluoroquinolone that behaves similarly. First-step mutants were obtained with both drugs but only at the MIC. These mutants exhibited distinctive small-colony phenotypes and two- to fourfold increases in MICs of NSFQ-105, sparfloxacin, and ciprofloxacin. No changes were detected in the quinolone resistance-determining regions of the gyrA, gyrB, grlA, or grlB gene. Quinolone-induced small-colony mutants shared the delayed coagulase response but not the requirement for menadione, hemin, or thymidine characteristic of small-colony variants, a subpopulation of S. aureus that is often defective in electron transport. Second-step mutants selected with NSFQ-105 had gyrA(S84L) alterations; those obtained with sparfloxacin carried a gyrA(D83A) mutation or a novel gyrB deletion (ΔRKSAL, residues 405 to 409) affecting a trypsin-sensitive region linking functional domains of S. aureus GyrB. Each mutation was associated with four- to eightfold increases in MICs of NSFQ-105 and sparfloxacin, but not of ciprofloxacin, which we confirm targets topoisomerase IV. The presence of wild-type grlB-grlA gene sequences in second-step mutants excluded involvement of topoisomerase IV in the small-colony phenotype. Growth revertants retaining mutant gyrA or gyrB alleles were quinolone susceptible, indicating that resistance to NSFQ-105 and sparfloxacin was contingent on the small-colony mutation. We propose that small-colony mutations unbalance target sensitivities, perhaps through altered ATP or topoisomerase levels, such that gyrase becomes the primary drug target. Breaking of target parity by genetic or physiological means eliminates the need for two target mutations and provides a novel mechanism for stepwise selection of quinolone resistance.